Physical Capital Adjustment within Spain : Long-Run and Short-Run Analysis - Spilimbergo, Antonio (IMF Working Papers; Working Paper, 2001)
This paper considers the adjustment of physical capital within a country in the long run and in the short run. It uses a unique data set on income, labor, human capital, and private and public physical capital in the Spanish regions over the past two decades. In the long run, the movement of physical capital is consistent with its estimated relative rates of return. In the short run, an adverse shock to a region results in a sharp drop in employment and a gradual decline of physical capital; the system returns to its initial capital/labor ratio after four years. The sharp drop in employment is consistent with the view that wages are rigid. The analysis of adjustment in the short run relies on a vector autoregression methodology in which shocks are identified as the interaction between oil prices and the share of manufacturing in a region's employment.